2022
DOI: 10.3389/fpsyg.2022.851812
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effect of Assisted Repeated Reading on Incidental Vocabulary Learning and Vocabulary Learning Self-Efficacy in an EFL Context

Abstract: The purpose of the current study was to investigate the effect of two types of repeated reading (i.e., assisted and unassisted) on incidental vocabulary learning of Iranian English as a Foreign Language (EFL) learners. In so doing, a sample of 45 intermediate EFL students from two intact classes of a language institute were selected as the participants. The two classes were randomly assigned to an unassisted group (N = 21) who were required to just read and an assisted group (N = 24) who were asked to read and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 64 publications
(99 reference statements)
2
8
0
Order By: Relevance
“…According to his findings, learners who encounter an unknown word more times in informative contexts are able to demonstrate significantly larger gains in vocabulary knowledge than learners who have fewer encounters with a new word. This is in line with Soleimani et al (2022) whose study revealed that repeated exposure to vocabulary leads to significant EFL vocabulary gains. Despite of this, there is an unknown boundary between word which has been recognized and the word which has been fully understood and learnt in the process of incidental vocabulary learning.…”
Section: Literature Reviewsupporting
confidence: 89%
“…According to his findings, learners who encounter an unknown word more times in informative contexts are able to demonstrate significantly larger gains in vocabulary knowledge than learners who have fewer encounters with a new word. This is in line with Soleimani et al (2022) whose study revealed that repeated exposure to vocabulary leads to significant EFL vocabulary gains. Despite of this, there is an unknown boundary between word which has been recognized and the word which has been fully understood and learnt in the process of incidental vocabulary learning.…”
Section: Literature Reviewsupporting
confidence: 89%
“…According to his findings, learners who encounter an unknown word more frequently in informative contexts demonstrate significantly greater gains in vocabulary knowledge than learners who encounter a new word less frequently. This is consistent with the findings of Soleimani et al (2022), who discovered that repeated exposure to vocabulary leads to significant EFL vocabulary gains. Despite this, there is an unknown boundary between a recognized word and a fully understood and learned the word in the process of incidental vocabulary learning.…”
Section: Resultssupporting
confidence: 92%
“…Thus, they can have the deeper understanding of the texts. Eventually, this made them independent readers where they do not need anymore the help of an adult that will guide them (Soleimani et al, 2022). Conversely, Guerin and Murphy (2015) concluded that students could uncover the meaning of texts through strategic reading whereby it increase their levels of selfdirected learning.…”
Section: Discussionmentioning
confidence: 99%